Bimodal tweet-texts as a communicative unit of the Internet genre of twitting (exemplified by Donald Trump’s Twitter) - Мелещенко, Ольга Олегівна (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2018)
The article investigates bimodal tweet-texts as a unit of communication in the Internet genre of twitting, which is generated on the Twitter platform. It provides a definition of a bimodal tweet-text as a communicative unit of the genre of twitting, which is attached to the Twitter platform ready-made, characterized by integrity and cohesion, and which employs semiotic resources of two modes: verbal and pictorial. It also distinguishes the types of bimodal attached tweet-texts which comprise graphic elements with verbal inclusions and photographic elements with verbal inclusions. The graphic elements of bimodal attached tweet-texts are divided into infographics and drawings. Infographics are used to create arguments to prove the Twitter user's point of view in the form of graphs, maps and diagrams representing corresponding facts. Drawings with verbal inclusions are represented by such genres as cartoons, e-cards and also such varieties of Internet memes as advice memes and animated cartoon memes. Furthermore, bimodal attached tweet-texts, which combine photographic elements and verbal elements, include animated or static photographs. Both drawings and photographic images interact with verbal inclusions, creating metaphors, allusions, pun, contrasts that suggest the value of the user's point of view, exerting emotional influence as well as causing a comic effect.